2018
DOI: 10.1016/j.devcel.2018.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain Determines Cilia Length, Motility, and Planar Position in the Left-Right Organizer

Abstract: The Xenopus left-right organizer (LRO) breaks symmetry along the left-right axis of the early embryo by producing and sensing directed ciliary flow as a patterning cue. To carry out this process, the LRO contains different ciliated cell types that vary in cilia length, whether they are motile or sensory, and how they position their cilia along the anterior-posterior (A-P) planar axis. Here, we show that these different cilia features are specified in the prospective LRO during gastrulation, based on anisotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 64 publications
1
23
0
Order By: Relevance
“…brachyury mutant mouse lines and homologous zebrafish no tail morphants support this reasoning, as do our unpublished results on the role of brachyury during LR development in Xenopus (Amack and Yost, 2004;King et al, 1998) ;Sabrina Kurz and MB, unpublished). In addition, mechanical strain has been recently shown to constitute a decisive physical force in LRO morphogenesis and function, namely cilia polarization and motility (Blum and Ott, 2018;Chien et al, 2018). Remarkably, strain is only effective when foxj1 is present; therefore, it would be interesting to analyze whether or not FGF signaling is a prerequisite of strain-mediated LRO morphogenesis and function as well.…”
Section: Discussionmentioning
confidence: 99%
“…brachyury mutant mouse lines and homologous zebrafish no tail morphants support this reasoning, as do our unpublished results on the role of brachyury during LR development in Xenopus (Amack and Yost, 2004;King et al, 1998) ;Sabrina Kurz and MB, unpublished). In addition, mechanical strain has been recently shown to constitute a decisive physical force in LRO morphogenesis and function, namely cilia polarization and motility (Blum and Ott, 2018;Chien et al, 2018). Remarkably, strain is only effective when foxj1 is present; therefore, it would be interesting to analyze whether or not FGF signaling is a prerequisite of strain-mediated LRO morphogenesis and function as well.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ciliated microorganisms can reorient the direction of ciliary 340 beating in the course of an avoidance reaction (Tamm et al, 1975). Mechanical strain has also been 341 shown to be involved in dictating cilia orientation, length and motility features (Chien et al, 2018). Our 342 study sheds a different light on these systems as it shows that cilia orientation is related to cell polarity in 343 a complex way that includes an intrinsic sense of chirality.…”
mentioning
confidence: 89%
“…This connection has only recently been made by studies in Xenopus. Chien et al [2018] have explanted presumptive skin or LRO tissues and applied artificial strain to explants, i.e., they have sucked explants into glass capillaries to mimic gastrulation strain forces, which would not have been possible in any other vertebrate model [Chien et al, 2015;Blum and Ott, 2018a]. Their work beautifully and convincingly showed that strain is required for generation of the PCP vector, for cilia lengthening, and motility.…”
Section: Doi: 101159/000490898mentioning
confidence: 99%